Evaluating hypoxia during air travel in healthy infants. Issue 12 (18th July 2013) - Khanna, Mansi; Shackleton, Claire; Verheggen, Maureen; Sharp, Mary; Wilson, Andrew C; Hall, Graham L
Abstract : Up to a third of ex-preterm infants flying near term exhibit pulse oxygen saturation (SpO2 ) of less than 85% during air travel. A hypoxia challenge test (HCT) is recommended to evaluate the requirement for in-flight supplemental O2 . The validity of the HCT in healthy, term infants has not been reported. This study aimed to characterise the in-flight hypoxia response and the accuracy of the HCT to predict this response in healthy, term infants in the first year of life. Infants (n=24: (15 male)) underwent a HCT prior to commercial air travel during which parents monitored SpO2 . Thirty-two flights were undertaken with six infants completing multiple flights. The median in-flight SpO2 nadir was 87% and significantly lower than the HCT SpO2 nadir (92%: p<0.001). Infants on seven flights recorded SpO2 <85% with one infant recording a HCT with a SpO2 less than 85%. There was marked variability in the in-flight SpO2 in the six infants who undertook multiple flights, and for three of these infants, the SpO2 nadir was both above and below 85%. We report that in healthy term infants an in-flight SpO2 below 85% is common and can vary considerably between flights and that the HCT poorly predicts the risk of in-flight hypoxia (SpO2 <85%). As it is common for healthy term infants to have SpO2 less than 85% during air travel further research is needed to clarify whether this is an appropriate cut-off in this age group.